Client's satisfaction in face-to-face counselling and cyber counseling approaches: a comparison - Zainudin, Zaida Nor; Mohamad Yusop, Yusni (Human Resource Management Academic Research Society, 2018)
This research is an attempt to explore the effectiveness of Cybercounseling services. In this research, the success of the Cybercounseling service is measured in terms of the capability of this method to provide client satisfaction (Client Satisfaction). This quasi-experimental study uses Non-equivalent Control Group Pretest/Postest Design. Quantitative data obtained using the Client's Satisfaction Inventory Short-Form (CSI-SF) questionnaire. A total of 60 research subjects were involved and conducted in two study groups, control group using Face-to-Counseling approach and experimental group using Cybercounseling approach. The findings show that Client Satisfaction in Cybercounseling approach is higher than Client Satisfaction in Face-to-face Counseling approach.